Identification of Differentially Expressed cDNA in Cassava under Drought Stress Using cDNA-RAPD Approach - Hartati, N Sri; Supatmi, Supatmi; Aryaningrum, Pramesti Dwi; Sudarmonowati, Enny (ANNALES BOGORIENSES, 2013)
Cassava is an important carbohydrate source that provides food security and alternative renewable energy development. This plant is naturally drought tolerant, but there is a wide variation within cassava genotypes in their ability to maintain high yield and starch production under drought stress. It has been reported that cassava clones with leaf retention or stay green trait can produce more total fresh biomass and high root dry matter compared to drought susceptible cultivars. The genetic, biochemical and molecular bases of stay green trait need to be understood to develop drought resistant cassava cultivars since water stress limits yield and starch production. Differential Display (DD)RT-PCR is a powerful technique for analyzing differences in gene expression. The method is based on the detection of the differentially expressed cDNAs from two or more samples. The main objective of this study was to identify differentially expressed cDNA in cassava under drought stress by employing a cDNA-RAPD approach. In this study, we used cassava genotype Ubi Kuning which was considered the most responsive to water insufficiency (45 days without watering). Leaf samples were collected from water stressed and well-watered plants at day 45. Among 11 random primers, OPB03 and OPH17 have identified differentially expressed cDNA in Ubi Kuning. Further characterization of these PCR products of expressed cDNA under drought stress may open possibility the development of cassava with improved drought resistance through genetic engineering and/or marker assisted selection (MAS).